A Relationship between Anterior Talar Migration in the Sinus Tarsi on Weightbearing Computed Tomography and Failure of the Talocalcaneal Interosseous Ligament in Progressive Collapsing Foot Deformity. Issue 1 (February 2023) - Kim, Jaeyoung; Mizher, Rami; Rajan, Lavan; Srikumar, Syian; An, Tonya; Palma, Joaquin; Zhu, Jiaqi; Sofka, Carolyn M.; Henry, Jensen; Demetracopoulos, Constantine; Ellis, Scott J.; Deland, Jonathan
Category: Hindfoot; Midfoot/Forefoot Introduction/ Purpose: Progressive collapsing foot deformity (PCFD) is a complex condition thought to be incited by ligament failure. The spring ligament has been extensively studied, and its reconstruction as part of the PCFD correction is becoming more popular. Failure of the interosseous ligament may also be a key contributor, although its role is less described. Since the advent of weightbearing computed tomography (WBCT), the sinus tarsi talocalcaneal relationship has been shown to correlate with the foot deformity as well as the ligament status surrounding the talus. This study aimed to identify when the interosseous and spring ligaments begin to fail in PCFD. Both WBCT and high-quality magnetic resonance imaging (MRI) were used to identify sinus tarsi morphologies involved in failure of the interosseous and spring ligaments. Methods: This study included 82 PCFD patients (mean age: 51.8 years) who underwent preoperative WBCT and MRI. Sinus tarsi morphology on WBCT was categorized into two major categories based on the anterior migration of the talus over the calcaneus on sagittal images: No-migration (Type 1) and Migration (Type 2). Then, a subgroup was established based on the presence of bony impingement: a: no-impingement; b: impingement (Figure 1). Two radiologists evaluated the status of the ligaments around the talus, including the spring and interosseous ligaments, as normal, insufficiency, or tear. On WBCT images, axial plane talocalcaneal subluxation was determined by comparing the talar and calcaneal axes to the transmalleolar axis. The status of the ligaments, degree of talocalcaneal subluxation and calcaneofibular impingement on WBCT, and four plain radiographic parameters of each type were compared. A weighted kappa test was used to determine the interrater reliability of the classification system among six observers. Results: Major categorization revealed distinct differences between the two types, with the migration type (n=38) demonstrating a larger prevalence of torn spring (superomedial: 47.4% and inferomedial: 42.1%) and interosseous (47.4%) ligaments, a greater degree of internal rotation of the talus and talocalcaneal subluxation, and a greater deformity on plain radiographs than the no- migration type (n=44, Table 1). Out of 21 patients with torn interosseous ligament, only 6 (28.6%) exhibited bony calcaneofibular impingement, and these were all Type 2b patients. Except for differences in Meary's angle and Talonavicular coverage angle between Type1a and Type1b, subtypes based on impingement did not exhibit significant differences on MRI, WBCT, or plain radiographic findings. Interrater reliability testing showed substantial agreement between observers, with a kappa of 0.792 (95% confidence interval: 0.713-0.877). Conclusion: While failure of the interosseous ligament is known to occur at the latest stage of PCFD when there is bone on bone calcaneofibular impingement, our study reveals that failure commences during the transition from moderate to severe deformities. This correlates with the anterior migration of the talar process relative to the angle of Gissane in the sagittal plane as well as talar internal rotation in the axial plane. These findings imply that like spring ligament reconstruction, interosseous ligament reconstruction may serve a role in correcting PCFD in somewhat earlier as well as more advanced stages.